Benefits of Pharmaceutical Care in care for breast cancer patients (Research, Society and Development, 2022)
Mana cancer is one of the pathologies that still lead thousands and women to death, being behind only cervical cancer. Diagnosis is often late, and treatment ends up being difficult. Chemotherapy treatments are the ones that bring many doubts to the patient. With the intention of alleviate this problem, pharmacist is the professional with greater capacity and knowledge regarding the attention needed to meet this group. Based on this principle that more knowledge is needed on the subject that this study aimed to realizer a systematic review pointing out the benefits of pharmaceutical care in the care of patients undergoing breast cancer treatment.  Regarding the methodology, the based study model was used in a qualitative approach through a systematic review of the literature. The method chosen was PRISMA (Preferred Reporting Items for Systematic Reviews and Metaanalyses).  The research was carried out in the databases of PubMed, VHL, MEDLINE, LILACS and SCIELO.  The selected papers had the profile of original articles, monographs, magazines, which had been published in the years 2015 to 2022 in the Portuguese, Spanish and English.  A total of 242,57 articles were found in the databases, however after the exclusion criteria were applications, 10 articles were selected. Through the findings, it was possible to observe how important is the role of the pharmaceutical professional in the care of the pharmaceutical care provided to breast cancer patients.  Because it brings safety to patients regarding pharmacological treatment, reduces doubts about medications as well as the interaction between them, thus reducing the difficulties in treatment adhering. The pharmacist contributes to the attention in the administration of medications, in the dispensation of medications, as well as in the guidelines on the use of them.